2019
DOI: 10.3389/fvets.2019.00360
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Clinical Trial in Dogs With Leptospirosis Treated With Enrofloxacin Hydrochloride-Dihydrate (ENRO-C)

Abstract: Pharmacokinetics of enrofloxacin HCl-2H2O (enro-C) in dogs and Monte-Carlo simulations against Leptospira spp. prompted a clinical study to treat the clinically apparent phase of this disease. Leptospirosis was diagnosed by real-time PCR from blood, micro-agglutination titers (MAT), clinical signs and blood parameters of the liver and kidney. In order to determine the clinical ability of the participants to diagnose leptospirosis on the first exam and establish an early treatment to avoid excessive organ damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Indeed, achieving therapeutic concentrations of enrofloxacin in the renal and reproductive tract when using enro-C requires confirmation, but the cure rates observed in this trial suggest it is possible. The decrease in the antibody titers observed after treatment with 15 mg/kg of enro-C follows the patterns reported by Gerritsen and colleagues [ 10 ] after administering a dose of 25 mg/kg/day of streptomycin and complies well with the previously reported efficacy of enro-C to treat dogs [ 21 ]. Hence, it is safe to assume that this trend toward reduction in antibody titers is associated with a decrease in or absence of bacteria, as Carrascosa et al [ 36 ] demonstrated in the hamster leptospirosis model.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, achieving therapeutic concentrations of enrofloxacin in the renal and reproductive tract when using enro-C requires confirmation, but the cure rates observed in this trial suggest it is possible. The decrease in the antibody titers observed after treatment with 15 mg/kg of enro-C follows the patterns reported by Gerritsen and colleagues [ 10 ] after administering a dose of 25 mg/kg/day of streptomycin and complies well with the previously reported efficacy of enro-C to treat dogs [ 21 ]. Hence, it is safe to assume that this trend toward reduction in antibody titers is associated with a decrease in or absence of bacteria, as Carrascosa et al [ 36 ] demonstrated in the hamster leptospirosis model.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison, enro-C is highly effective against Leptospira spp. in the hamster model [ 36 ] and clinical cases in dogs [ 21 ]. However, neither enro-C nor other fluoroquinolones were tested in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoroquinolones were routinely unsuccessful in this group of dogs, in contrast to the results of a recent study. 25 It is possible that geographical variables in the strains of Leptospira spp. contribute to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Ketepatan diagnosa dari infeksi ini sangat penting dalam manajemen kasus kaitannya dengan pilihan antibiotik saat pengobatan. Diagnosis dini leptospirosis pada anjing harus dilakukan karena sifat zoonosisnya dari penyakit dan kebutuhan untuk memulai intervensi dalam langkah awal pelaksanaan terapi pada anjing yang terinfeksi secara tepat (Gutierrez 2019). Diferensial diagnosa canine leptospirosis diantaranya penyakit cacing jantung (heartworm disease), autoimmune he mo lytic anemia, bacteremia, infectious canine hepatitis virus, hepatic neoplasia, trauma, lupus, Rocky Mountain spotted fever, Ehrlichiosis, toxoplasmosis, renal neoplasia, dan renal calculi (Nilufer 2004).…”
Section: Pendahuluanunclassified